A Comprehensive Review of the Development and Therapeutic Use of Antivirals in Flavivirus Infection - Aarti Tripathi; Shailendra Chauhan; Renu Khasa (Viruses)
Flaviviruses are a diverse group of viruses primarily transmitted through hematophagous insects like mosquitoes and ticks. Significant expansion in the geographic range, prevalence, and vectors of flavivirus over the last 50 years has led to a dramatic increase in infections that can manifest as hemorrhagic fever or encephalitis, leading to prolonged morbidity and mortality. Millions of infections every year pose a serious threat to worldwide public health, encouraging scientists to develop a better understanding of the pathophysiology and immune evasion mechanisms of these viruses for vaccine development and antiviral therapy. Extensive research has been conducted in developing effective antivirals for flavivirus. Various approaches have been extensively utilized in clinical trials for antiviral development, targeting virus entry, replication, polyprotein synthesis and processing, and egress pathways exploiting virus as well as host proteins. However, to date, no licensed antiviral drug exists to treat the diseases caused by these viruses. Understanding the mechanisms of host–pathogen interaction, host immunity, viral immune evasion, and disease pathogenesis is highly warranted to foster the development of antivirals. This review provides an extensively detailed summary of the most recent advances in the development of antiviral drugs to combat diseases.